2017
DOI: 10.1055/s-0043-117416
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hyperosmolarity on Long-Term Outcome in Patients Presenting with Severe Hyperglycemic Crisis: A Population Based Study

Abstract: Infection, use of furosemide and benzodiazepines may be important precipitating factors of HHS. Prospective clinical trials are mandatory to analyze the safety of ACE-inhibitors and benzodiazepines in elderly patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Our study also found HHS occurs more commonly in elderly female patients, with the majority of patients having infections as the leading precipitating factor. As reported in previous studies, advanced age, male gender, high glucose, high leukocyte count, low bicarbonates, and altered mental status were associated with increased mortality of HHS [ 8 , 34 ]. In our study, we revealed a novel prognostic factor and a new protective factor for HHS patients.…”
Section: Discussionmentioning
confidence: 58%
“…Our study also found HHS occurs more commonly in elderly female patients, with the majority of patients having infections as the leading precipitating factor. As reported in previous studies, advanced age, male gender, high glucose, high leukocyte count, low bicarbonates, and altered mental status were associated with increased mortality of HHS [ 8 , 34 ]. In our study, we revealed a novel prognostic factor and a new protective factor for HHS patients.…”
Section: Discussionmentioning
confidence: 58%
“…Among adult T2D patients, HHS at diagnosis was associated with older age compared with control [29]. Older patients may not recognize diabetes symptoms, similar to younger children.…”
Section: Discussionmentioning
confidence: 88%
“…Local and systemic osmotic alterations have been associated with a number of disorders, such as brain injury (Kawamata et al, 2007), hyper-/hyponatremia state (Reynolds et al, 2006), inflammatory and infectious processes (Brocker et al, 2012), renal failure (Kuwabara et al, 2017), and diabetes (Umpierrez and Korytkowski, 2016). The hyperglycemic hyperosmolar state (HHS) is a serious acute complication of diabetes decompensation, especially in type 2 diabetes mellitus (T2DM), with critical prognosis and a repercussion for renal failure (Johnson et al, 2014;Pasquel and Umpierrez, 2014;Umpierrez and Korytkowski, 2016;Kruljac et al, 2018). Given the well-known interrelationship between osmolality, glycemia, and kidney transport function, it is plausible to hypothesize that part of the biological effect of glucose at high concentrations can be attributed to its osmotic action, which has not been directly investigated in the context of the paracellular barrier function (Aluksanasuwan et al, 2017;Kruljac et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The hyperglycemic hyperosmolar state (HHS) is a serious acute complication of diabetes decompensation, especially in type 2 diabetes mellitus (T2DM), with critical prognosis and a repercussion for renal failure (Johnson et al, 2014;Pasquel and Umpierrez, 2014;Umpierrez and Korytkowski, 2016;Kruljac et al, 2018). Given the well-known interrelationship between osmolality, glycemia, and kidney transport function, it is plausible to hypothesize that part of the biological effect of glucose at high concentrations can be attributed to its osmotic action, which has not been directly investigated in the context of the paracellular barrier function (Aluksanasuwan et al, 2017;Kruljac et al, 2018). Interestingly, we have shown in a previous work that acute (24 h) and chronic (72 h) exposure to high glucose, at concentrations that simulate hyperglycemia in prediabetic (180 mg/dL) and diabetic (360 mg/dL) patients, induces changes in tubular epithelial barrier function mediated by TJ in a concentration and time-dependent manner in the renal Madin-Darby Canine Kidney (MDCK) cell line (Mongelli-Sabino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%